Pelabelan Total Super (a,d)-Sisi Antimagic Pada Graf Buah Naga - Nurvitaningrum, Agnes Ika; Dafik, Dafik; Setiawani, Susi (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph G is called an (a,d)-edge-antimagic total labeling if there exist a one-to-one mapping f : f(V)={1,2,3,...,p} → f(E)={1,2,…,p+q} such that the edge-weights, w(uv)=f(u)+f(v)+f(uv), uv E(G), form an arithmetic progression {a,a+d,a+2d,…,a+(q-1)d}, where a>0 and d0 are two fixed integers, form an arithmetic sequence with first term a and common difference d. Such a graph G is called super if the smallest possible labels appear on the vertices. In this paper we recite super (a,d)-edge-antimagic total labelling of connected Dragon Fruit Graph. The result shows that Dragon Fruit Graph have a super edge antimagic total labeling for d0,1,2.